Yield performance of MD2 pineapple when intercropped with different rubber clone / Amir Suffizad Abu Hanifah - Abu Hanifah, Amir Suffizad (Faculty of Plantation and Agrotechnology, 2019)
Intercropping is the practice of growing different crops in the same field. The practice is very common especially among smallholder to maximize the usage of their land. Intercropping with shorter duration annual and perennial plant give one step of masking the gap in earnings which smallholder suffer while they replant main crop. There are ample of research study conducted to find the suitability of many combination of crop to intercrop to a certain piece of land including pineapple crop. However several researches had been done about pineapple with different clone of rubber. Different type of rubber clone may affect the end product of MD2 pineapple total weight when harvested because the different physiological characteristic of the crop. The case study is done to find if there is any different result of yield of MD2 in the field and the suitability of different rubber clone intercropped with MD2 pineapple. The study is run using primary data and collected in Jelebu, Negeri Sembilan. The result is based from the total and mean yield gain from the plot that is intercropped. The data were interpreted with one-way analysis of variance (ANOVA) analysis by using the Statistical Package for Science Social (SPSS). Results showed that there is no relationship between the variable, the yield of MD2 pineapple when intercropped with different rubber clone, hinting that there is substitutes in planting different rubber clone during intercropped but several aspect during growth and maturity can be further improved to acquire more precise result from the field. The highest yield gain when intercropped with Hevea benthamiana, and the lowest with RRIM 600.